Processing of Cow Manure Waste as Organic Fertilizerin Farmer Groups in Towara Village, Galela District,North Halmahera Regency (Agrikan Jurnal Agribisnis Perikanan, 2022)
The Independent Livestock Farmer Group currently consists of 15 members and is one of the farmer groups in Towara Village, Galela District, North Halmahera Regency. However, these farmer groups have not been able to process cow dung into organic fertilizer, and the traditional livestock farming system carried out by livestock farmer groups has resulted in low income for the husbandry businesses. The community service implementation team plays an active role in helping to improve the understanding and skills of farmer groups regarding optimal waste utilization through counseling, technical guidance, and demonstration plots with this Community Partnership Program (PKM) (demplot) activity. The community partnership program has been welcome and accepted by all group members and the rest community, and it was hoped to increase knowledge and understanding of organic fertilizer processing will have a positive impact on farmers' income.
Keywords: Waste treatment; cow manure dung; counseling; organic fertilizer